Clinicopathological Spectrum of Intracranial Space-Occupying Lesions: A Tertiary Care Center Experience (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Intracranial space-occupying lesions (ICSOLs) comprise a heterogeneous group of neoplastic and non-neoplastic conditions with variable clinical presentation and biological behavior. Histopathological examination remains the gold standard for definitive diagnosis and grading, which directly influence management and prognosis.Aim & Objectives:   To evaluate the demographic profile, clinical presentation, histopathological spectrum, and WHO grade distribution of ICSOLs in a tertiary care center, and to assess associations between clinical features, lesion type, and tumor grade.Material & Methods: This descriptive observational study included 100 consecutive ICSOL cases received in the Department of Pathology in collaboration with Neurosurgery. Clinical details and radiological information were recorded. Tissue specimens obtained by biopsy or excision were processed routinely and stained with hematoxylin and eosin; special stains and immunohistochemistry were performed where required. Lesions were classified according to WHO CNS tumor classification, and gliomas/meningiomas were graded as per WHO criteria. Data were analyzed using descriptive statistics, and χ² tests were applied to examine symptom–lesion associations and compare grade distribution; p < 0.05 was considered significant.Results: Mean age was 41.3 ± 18.7 years (range 2–70), with a peak in 31–40 years (22%). There was marginal male predominance (52%). Neoplastic lesions predominated (95%). Gliomas were most common (30%), followed by meningiomas (24%) and schwannomas (15%). Headache was the commonest symptom (62%), followed by seizures (34%) and visual disturbance (28%). Significant symptom associations were observed for headache, seizures, visual disturbance, focal neurological deficit, and fever (p < 0.05). WHO grade distribution differed significantly between gliomas and meningiomas, with high-grade tumors (Grade III–IV) significantly more frequent among gliomas (χ² = 14.22, p = 0.00016).Conclusion: ICSOLs in this cohort were predominantly neoplastic, with gliomas and meningiomas forming the major tumor burden. Clinicopathological correlations and WHO grading provide valuable diagnostic and prognostic insights, reinforcing the central role of histopathology in resource-limited settings.